Relevansi Kurikulum Hospitality Politeknik Pariwisata Makassar Terhadap Restoran Di Sulawesi Selatan - Arifin, Muhammad; Badollahi, Muh Zainuddin (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2019)
The curriculum has a position and a very important position in the education process, the curriculum is a requirement and an inseparable part of the education itself. Through the curriculum can provide the competencies needed by the world of work to students, so it is necessary for students to graduate they will be easily absorbed in the world of work in accordance with the competencies that they got during college. The purpose of this research is to see the relevance of the curriculum in the management of study programs for restaurants in South Sulawesi. The method used in this study is a quantitative approach. Based on the results of the study found that the existing curriculum is relevant to restaurants this can be measured by the absorption of alumni who work in the hotel and restaurant sector as much as 98.94%. in addition, the waiting time for alumni to get an average job is 3-6 months. Relevant competence, it is expected that the Department of Hospitality Management Study Program of Makassar Tourism Polytechnic produces good products that are ready for work. Materials that are highly relevant to the needs of work must be maintained or improved because competition in the workforce is very fierce.